2020
DOI: 10.1021/acs.analchem.0c00478
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Using Protease Alternatives to Trypsin Benefits from Sequential Digestion with Trypsin

Abstract: Trypsin is the most used enzyme in proteomics. Nevertheless, proteases with complementary cleavage specificity have been applied in special circumstances. In this work, we analyzed the characteristics of five protease alternatives to trypsin for protein identification and sequence coverage when applied to S. pombe whole cell lysates. The specificity of the protease heavily impacted the number of proteins identified. Proteases with higher specificity led to the identification of more prot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 23 publications
0
36
0
Order By: Relevance
“…Another 50 μL of 50 mM ABC buffer was added to gel samples and incubated at 37 °C for overnight. After that, elastase (Promega) (150 ng/μL in water) was added to the final concentration of 7.5 ng/μL and incubated for 30 min at 37 °C (Dau et al, 2020). Digestion was stopped by the addition of 5 μL of 10% TFA.…”
Section: Immunoprecipitationmentioning
confidence: 99%
“…Another 50 μL of 50 mM ABC buffer was added to gel samples and incubated at 37 °C for overnight. After that, elastase (Promega) (150 ng/μL in water) was added to the final concentration of 7.5 ng/μL and incubated for 30 min at 37 °C (Dau et al, 2020). Digestion was stopped by the addition of 5 μL of 10% TFA.…”
Section: Immunoprecipitationmentioning
confidence: 99%
“…The use of multiple proteolytic enzymes to increase proteome coverage has been reported previously [ 52 , 53 , 54 ] and a recent study showed that dual proteolytic treatment with Trypsin followed by Asp-N increased protein IDs in a yeast proteomics experiment by roughly 10% [ 55 ]. While the NGAG protocol does utilize both enzymes, the steps between these proteolysis treatments include blocking of endogenous Asp residues from Asp-N cleavage by treatment with aniline.…”
Section: Discussionmentioning
confidence: 99%
“…Other proteases such as chymotrypsin, endoproteinase Glu-C, Asp-N and Lys-C, are equally useful for comprehensive glycoproteomics, due to their complementary cleavage specificities [62]. Using dual-protease approaches often increases glycoprotein identification and sequence coverage for the in-depth characterisation of the glycoproteome [63][64][65].…”
Section: Proteolytic Digestion Of Complex Glycoprotein Mixturesmentioning
confidence: 99%